"Static Analysis of Multi Layers RC Deep Beams Under Combined Shear and Torsion " (Journal of Architectural Design, 2023)
This research aims at evaluating the performance of reinforced concrete layered (hybrid) deep beams under the combined action of shear and torsion through finite element modelling using ABAQUS / CAE 2019. Concrete damage plasticity was used with meshing of a reduced integration 8-nodes linear brick element for concrete elements and a linear two-node truss element with three degrees of freedom was used for steel elements. Initially, shear and torsion models were created from experimental results of previous works on solid normal reinforced concrete deep beams. The validation of numerical results against experimental results showed mean values of 0.97, and 0.96 for at ultimate load and torque. Several hybrid deep beam were modelled from two types of concrete, fiber reinforced concrete and ultra-high strength concrete (UHSC) added in layers to normal concrete separately from 0 to 1300 mm (full thickness) with 100 mm increment each time. The simulation results indicated that the increase in the thickness of fiber reinforced concrete transferred the failure mode from single to many diagonal cracks with more detectable cracks. The mode of failure changed from combined shear and torsion to more of a torsion failure and was more pronounced for UHSC deep beams. In general, UHSC hybrid layer deep beams performed better than fiber reinforced concrete deep beams due to lower propagated damages and substantially higher ultimate loads and torques with 600 to 800 mm of each hybrid layers in the tension area provided the best behaviour. The ABAQUS software was able to accurately predict the performance of deep beams under the combined action of shear and torsion